Experimental study of the effect of the state of charge on self-heating ignition of large ensembles of lithium-ion batteries in storage. (25th July 2022) - He, Xuanze; Hu, Zhenwen; Restuccia, Francesco; Fang, Jun; Rein, Guillermo
Highlights: Both the cell thermal runaway temperature ( T c, c ) and critical ambient temperature ( T a, c ) triggering ignition decrease as SOC increases. The T c, c is independent of the number of cells, while the T a, c decreases as the number of cells increases. The T a, c should be use to guide storage rather than the standard suggested critical temperature increase rate, which does not represent the criticality of ignition. The laboratory results are upscale to predict the T a, c using storage. Abstract: Self-heating can cause the ignition of open-circuit Lithium-ion batteries. Current safety literature focuses on the self-heating chemistry of a single cell, ignoring the effects of heat transfer. However, a large ensemble of batteries has a non-uniform temperature distribution and therefore self-heating ignition is dominated by both heat transfer and chemistry. This type of ignition is of importance when batteries are stored for long periods of time and in large ensembles but has been rarely studied to date. This paper studies the effect of the state of charge (SOC) on the self-heating behavior of LiCoO2 prismatic cells. The SOC of 0% (of interest in the safety of waste facilities), 30% (transport), 50% (storage), 80% (aged battery) and 100% (fully-charged battery), and 1, 2 and 4 cells stacked together were studied using oven experiments. Results show that cells at all SOC can self-ignite. Flames were only observed for SOC larger than 80%. We compare two temperature criteria: the temperature of the middle cell using the critical increase rate of 10 ℃/min defined in standard SAE-J2464, and the ambient temperature around the ensemble when triggering ignition. Both temperature criteria decrease with increasing SOC showing that the hazard grows with energy density. The cell temperature criterion is independent of the number of cells, while the ambient temperature criterion decreases as the number of cells increases, which indicates the increased risk of self-heating ignition when cells are stacked together in ensembles. Thus, the ambient temperature criterion should be used to design safe storage rather than the standard cell temperature increase rate, which does not represent well the criticality of ignition. The effective kinetics and thermal properties at different SOCs are extracted based on the Frank-Kamenetskii theory and are used to upscale laboratory results to storage conditions. The results in this work can improve the safety of the storage and provide scientific insight for safety standards.